Power, the Economic Environment, and Social Choice - Saposnik, Rubin (Econometrica, 1974)
[The economic environment (social output) is treated explicitly as a social choice variable. Individual orderings over the set of environments are derived from maximizing behavior. The influence of each individual on the choice made by society is expressed in terms of a power indice which is itself a function of the prevailing environment. These individual power indices give rise to a power rule which provides a social ordering over the set of environments, with the social choice set under any environment being non-empty. The existence of equilibrium in terms of the power rule is established.]